Performance analysis of OFDM technology on radio-over-fiber systems - Ravach, Tashi Arthur (2013)
Dissertação de mest., Engenharia Eletrónica e Telecomunicações, Faculdade de Ciências e Tecnologia, Univ. do Algarve, 2011